25th Annual Conference of the International Group for Lean Construction 2017
DOI: 10.24928/2017/0272
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Lean Methods in Mining Development Projects

Abstract: One of the main challenges that developing countries face is the need to increase productivity. In Chile, the most important productivity gap in both mining and construction industries is the lack of operational efficiency, caused mainly by the low adoption of advance management methods. Hence, considering the need to increase productivity through operational efficiency, lean production emerges as a management system with the objective to create value while eliminating waste, and continuously seek operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…In this study, we set out to assess the importance of design process stability and reliability by comparing three key parameters: (1) BS, (2) TT and (3) PPC level. A comparison of the findings with those of previous studies confirmed the positive effect of PPC on process stability in design processes (Alarcón et al 2008;Baladrón & Alarcón 2017). These results also corroborate the findings of previous work by El-Samad et al (2017), who suggested that new metrics should be developed for LPS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, we set out to assess the importance of design process stability and reliability by comparing three key parameters: (1) BS, (2) TT and (3) PPC level. A comparison of the findings with those of previous studies confirmed the positive effect of PPC on process stability in design processes (Alarcón et al 2008;Baladrón & Alarcón 2017). These results also corroborate the findings of previous work by El-Samad et al (2017), who suggested that new metrics should be developed for LPS.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies (Alarcón et al 2008;Baladrón & Alarcón 2017) have examined the relationship between process stability and PPC. The authors observed a relationship between high PPC and the stability of construction and mining processes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the collection of the empirical material for this study, new articles have been published on the subject (Baladrón and Alarcón, 2017; Ghodrati et al , 2017; Lanke et al , 2016; Mikhalchenko et al , 2016; Yuan et al , 2016). Although several of them make important contributions, many also still focus on few, certain techniques and in general reflect the issues highlighted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar effort to investigate lean adoption practices in South America, Baladron and Alarcon (2017) evaluated the impact of lean implementation in mining projects in Chile during their execution phase. The authors investigated how lean methodologies could affect the performance of mining projects using key indicators such as workable time, daily physical progress, program completion and the relationship between activities completed and planned.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%